2022
DOI: 10.1128/iai.00211-22
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Regulator SpxA1 Influences the Morphology and Virulence of Listeria monocytogenes

Abstract: Listeria monocytogenes is a Gram-positive facultative anaerobe and an excellent model pathogen for investigating regulatory changes that occur during infection of a mammalian host. SpxA1 is a widely conserved transcriptional regulator that induces expression of peroxide-detoxifying genes in L. monocytogenes and is thus required for aerobic growth.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Interestingly, uptake of Lm was unchanged in Tlr2 −/− BMDMs compared to WT BMDMs (S4B Fig). While we did not directly test Tlr5 −/− macrophages, studies from our lab have found that Lm lacking the TLR5 ligand flaA are taken up by macrophages with equal efficiency as wildtype Lm (40). To account for the possibility of redundancy between TLR2 and TLR5, we infected wildtype and Tlr2 −/− BMDMs with Δ flaA and found that uptake remained unchanged in the absence of TLR2 and TLR5 recognition (S4C Fig).…”
Section: Resultsmentioning
confidence: 93%
“…Interestingly, uptake of Lm was unchanged in Tlr2 −/− BMDMs compared to WT BMDMs (S4B Fig). While we did not directly test Tlr5 −/− macrophages, studies from our lab have found that Lm lacking the TLR5 ligand flaA are taken up by macrophages with equal efficiency as wildtype Lm (40). To account for the possibility of redundancy between TLR2 and TLR5, we infected wildtype and Tlr2 −/− BMDMs with Δ flaA and found that uptake remained unchanged in the absence of TLR2 and TLR5 recognition (S4C Fig).…”
Section: Resultsmentioning
confidence: 93%
“…Following elution, peptides were completely dried under vacuum and resuspended in 0.1% (v/v) formic acid to a final concentration of ∼0.5 µg/mL. Samples were transferred into autosampler vials and subjected to mass spectrometry analysis using an Orbitrap Eclipse mass spectrometer (Thermo Scientific) as described (101). Raw spectral data were processed in MaxQuant using the Homo sapiens reference protein library (UniProt) and relative protein abundances were determined using the label-free quantification (LFQ) intensity method as described (101).…”
Section: Methodsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 7, 2023. ; https://doi.org/10.1101/2023.03.07.531620 doi: bioRxiv preprint 22 described (101). Raw spectral data were processed in MaxQuant using the Homo sapiens reference protein library (UniProt) and relative protein abundances were determined using the label-free quantification (LFQ) intensity method as described (101).…”
Section: Whole-cell Proteomicsmentioning
confidence: 99%
“…To test this hypothesis, we measured uptake of Lm and PI3K activation in Tlr2 -/macrophages. For these studies, BMDMs from Tlr2 -/mice were isolated and absence of TLR2 was confirmed by immunoblot analysis (S5A Fig) . Interestingly, uptake of Lm was unchanged in Tlr2 -/-BMDMs compared to WT BMDMs (S5B Fig) . While we did not directly test Tlr5 -/macrophages, studies from our lab have found that Lm lacking the TLR5 ligand flaA are taken up by macrophages with equal efficiency as wildtype Lm [40]. To account for the possibility of redundancy between TLR2 and TLR5, we infected wildtype and Tlr2 -/-BMDMs with ΔflaA and found that uptake remained unchanged in the absence of TLR2 and TLR5 recognition (S5C Fig) . These results indicate that phagocytosis of Lm is TLR-independent.…”
Section: Class 1a Pi3k Activation Is Required For Lm Phagocytosis By ...mentioning
confidence: 99%